Exact constants in Jackson-type inequalities for $L_2$-approximation on an axis - Doronin, V. G.; Ligun, A. A. (Ukrains’kyi Matematychnyi Zhurnal, 2009)
We investigate exact constants in Jackson-type inequalities in the space $L_2$ for the approximation of functions on an axis by the subspace of entire functions of exponential type.